GC-MS ANALYSIS OF ETHANOLIC EXTRACT OF ROOTS Of RUBIA CARDIFOLIA (MANJISTHA). - GAZI, SHAIKH; Ali, Sadath; Luqman, Shaikh; Rizwan, Syed Hussain (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The present research investigation was carried out with prime objective of studying the phytoconstituents of roots of Rubia Cardifolia after isolation with flash chromatography technique. Methods: The ethanolic root extract of Rubia Cardifolia was employed for GC-MS study. Results: The study on active principles of ethanolic root extract of Rubia Cardifolia by GC-MS, showed the presence of two important compounds. Rubiadin (30.81% area) and Purpurin (11.45 % area). More compounds would have appeared, but trying GC-MS with the isolated pure fraction by flash chromatography of root extract lead to isolation and discovery of two principal compounds. Conclusion: GC-MS analysis after carrying flash chromatography of ethanolic root extract led to identification of 02 pure compounds. The compounds were found to be Rubiadin (1, 3 dihydroxy 2 methyl anthraquinone) and Purpurin (1, 2, 4 trihydroxy anthraquinone). The presence of Rubiadin and Purpurin justifies the usage of the root extract of plant for treatment of skin ailments. Key words: GC-MS, Rubia Cardifolia, Psoriasis, Rubiadin, Purpurin